2010
DOI: 10.1051/kmae/2010002
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of experimental fluid mechanics to the design of vertical slot fish passes

Abstract: Key-words:vertical slot fish pass, flow topology, velocity field, turbulent kinetic energy This paper presents the main results of an experimental study of mean and turbulent characteristics of flow in a scale model of a vertical slot fish pass with varying width and slope (from 5% to 15%). Experimental hydraulic modelling was combined with the study of fish behaviour in the model. The discharge coefficient, which significantly affects the design of such facilities, varied from 0.67 to 0.89 and was strongly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 17 publications
4
57
0
3
Order By: Relevance
“…Besides recent observations in VSF's show that fish may take advantage of the unsteady character of the turbulent flow [19].…”
mentioning
confidence: 82%
“…Besides recent observations in VSF's show that fish may take advantage of the unsteady character of the turbulent flow [19].…”
mentioning
confidence: 82%
“…HOTCHKISS 2002, NIKORA et al 2003, WEBB and COTEL 2011. Recent observations showed that fish may further take advantage of the unsteady character of the turbulent flow (LIAO et al 2003, WANG et al 2010. The present investigation was motivated by the needs to facilitate upstream passage of small-bodied Australian native fish species in box culverts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the simplification of the study of fishways is a widespread problem and, in many cases, their performance is modeled according to uniform conditions (Rajaratnam et al, 1986;Wu et al, 1999;Puertas et al, 2004;Bermudez et al, 2010;Wang et al, 2010;Tarrade et al, 2011;among others).…”
Section: Introductionmentioning
confidence: 99%